Ixodid ticks and tick-borne infections in the Republic of Cuba - literature review and rationale for risk assessment - M. A. Khasnatinov; L. V. Rychkova; G. I. Rodriguez; G. B. Corona; G. A. Danchinova (Acta Biomedica Scientifica, 2018)
The Republic of Cuba is a popular destination for Russian tourists and about 30-50 thousands of Russian citizens visit Cuba annually. However, the recreational activity is often associated with the risk of Ixodid ticks bites and infection with tick-borne pathogens. According to published literature, the fauna of the hard tick in Cuba is represented by nine species including Ixodes capromydis, Amblyomma albopictum, A. cajennense, A. dissimile, A. quadricavum, A. torrei, Dermacentor nitens, Rhipicephalus sanguineus and R. (Boophilus) microplus. Five of these species, i.e. A. cajennense, A. dissimile, D. nitens, R. sanguineus and R. (Boophilus) microplus, were reported as human parasites. Ticks are spread over the most part of the island territory. Several tick-borne pathogens should be considered as a potential threat for the bitten humans in Cuba, including Borrelia burgdorferi sensu lato, Rickettsia sp., Anaplasma sp., Ehrlichia sp., Coxiella sp., thogotovirus and Crimean-Congo hemorrhagic fever virus. Implications for the epidemiology of tick-borne infections in the Russian Federation are discussed.